EVALUASI UNJUK KERJA IOT, SISTEM KONTROL DAN MONITORING SUHU DAN KELEMBAPAN PADA RUANG FREEZER MENGGUNAKAN APLIKASI BLYNK (STUDI KASUS PADA PT. AEROFOOD ACS DENPASAR) - Krisna Mahendra, Made; Dyana Arjana, I Gede; Suartika, I Made (Jurnal SPEKTRUM, 2023)
The implementation of temperature control and monitoring system in the freezer room at PT Aero Food ACS company plays a crucial role in maintaining the quality of stored food raw materials. Therefore, an appropriate and efficient control system is required to preserve the quality of stored meat. To address this, a system was developed using IoT-based Blynk application for control and monitoring, utilizing WEMOS as the microcontroller and DHT22 as the sensor. Before the system is deployed in the company, a performance test and evaluation are necessary to ensure that the system functions correctly and complies with the company's SOP. During the testing phase, the control system operated well and was in accordance with the company's SOP.